2015
DOI: 10.2485/jhtb.24.249
|View full text |Cite
|
Sign up to set email alerts
|

MC3T3-E1 Cell Assay on Collagen or Fibronectin Immobilized Poly (Lactic Acid-ε-Caprolactone) Film

Abstract: In the present study, collagen (Coll) or fibronectin (FN) was immobilized onto poly(lactic acid)/ -caprolactone (PLCL) copolymer surface and the attachment and proliferation of osteoblast-like cells on Coll or FN immobilized PLCL (Coll-PLCL, FN-PLCL) were evaluated. Coll or FN immobilized PLCL was prepared through a condensation reaction between the carboxylic acid groups on the hydrolyzed PLCL (PLCL-COOH) surface and the amino groups of Coll or FN using water soluble carbodiimide. The contact angle of the PLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…There were no significant differences in the adhesion cells among the three different PLCL50 films after 7 days (p > 0.05) . The results were consistent with previous studies after 90 min (23) . Even if the proportion of PLA was decreased in the film, the effects of cell adhesionpromoting and cell adhesioninhibiting were confirmed after three days.…”
Section: Mineralization Of Cellssupporting
confidence: 94%
See 2 more Smart Citations
“…There were no significant differences in the adhesion cells among the three different PLCL50 films after 7 days (p > 0.05) . The results were consistent with previous studies after 90 min (23) . Even if the proportion of PLA was decreased in the film, the effects of cell adhesionpromoting and cell adhesioninhibiting were confirmed after three days.…”
Section: Mineralization Of Cellssupporting
confidence: 94%
“…Ho et al (20) reported that many adhesive proteins' RGDS (Arg -Gly -Asp -Ser) peptide was immobi- films. As a result, Alb immobilized -PLCL25 films did not enhance the number and spread of the cells like FNimmobilized PLCL25 films (23) . Alb is a main plasma protein known as a cell adhesion inhibitory protein in contrast to FN and collagen (24,25) .…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Additionally, the collagen contact angle to PLCL film was approximately 56° in previous studies (19) .…”
Section: Mc3t3 -E1cells Adhesion On Filmsmentioning
confidence: 57%
“…collagen and the carboxylic acid groups on the hydrolyzed PLA using watersoluble carbodiimide. In our previous study, we reported that the number of attached MC3T3 -E1 cells to collagen -PLCL or FN -PLCL significantly accelerated compared with PLCL at 90 min and 3 and 7 days (19) . The number of MC3T3 -E1cells attached to the PSColl -PLA and TFColl -PLA films increased compared with the PLA film during 90 min, 3 and 7 days cell assay (p < 0.05) .…”
Section: Mc3t3 -E1cells Adhesion On Filmsmentioning
confidence: 89%